2C.05: CAN WE USE THE CONCEPT OF "ARTERIAL AGING" TO PREDICT BLOOD PRESSURE LEVELS?. (June 2015) - Weber, T.; Fitscha, P.; Hametner, B.; Wytrzens, C.; Wassertheurer, S.; Kellermair, J.; Eber, B.
Abstract : Objective: Arterial aging is one of the fundamental mechanisms underlying blood pressure (BP) increase, and may even precede BP rise. We hypothesized that the extent of arterial aging, quantified as aortic pulse wave velocity (aPWV) graded according to an age-specific reference group with normal BP, would be related to blood pressure classification, based on office and 24 hour ambulatory BP. Design and method: We measured BP and aPWV twice in the doctors office and performed 24 hour ambulatory BP monitoring with the oscillometric cuff-based mobilograph device (iem, Stolberg, Germany) in untreated and treated patients from a large group practice in internal medicine. APWV was estimated with the recently validated ARCSolver algorithm, based on age, systolic BP and waveform characteristics and was classified as < 50., 51.-95., and > 95 percentile of the age-specific reference group. Results: We included 839 patients (46.4% females, mean age 58.1 years, range 15–94 years). Mean office BP was 139/90 mm Hg, mean 24 hour BP was 128/80 mm Hg, mean aPWV was 9.6 m/sec. 247 patients were normotensive, 113 had white coat hypertension, 99 masked hypertension, and 380 were sustained hypertensive. 78.4% of the patients had aPWVs above the 95. percentile, 18.8% were between 50. and 95. percentile, and 2.7% were below the 50. percentile. There was a clear increase in the percentage of patients with sustained hypertension across the three categories of arterial aging (4.3%, 16.5%, and 53.6% in patients below the 50. percentile, between 50. and 95., and above the 95. percentile, respectively), and an inverse distribution related to normotension (Table). The differences were statistically highly significant (p < 0.0001). The relatively high percentage of patients with masked hypertension in the group < 50. percentile (30.4%) is of concern, but the absolute number is small (n = 7). Conclusions: Arterial aging, based on age-specific percentiles, may be a useful screening tool for sustained hypertension, based on office and 24 hour ambulatory BP. Figure. No caption available.